2009
DOI: 10.2135/cropsci2009.06.0333
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Germplasm Types of Tall Fescue and Orchardgrass to Different Cropping Environments of the Mediterranean Region

Abstract: Understanding of adaptation targets, selection environments, genetic resources, and plant types is required in breeding tall fescue [Lolium arundinaceum (Schreb.) S.J. Darbysh.] and orchardgrass (Dactylis glomerata L.) for Mediterranean environments prone to drought stress. Fourth‐year forage yield of seven orchardgrass and five fescue cultivars grown in Algeria and Sardinia revealed (i) crossover cultivar × location interaction in orchardgrass, with dormant germplasm performing best in the drier Algerian site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
20
2
1
Order By: Relevance
“…Crossover GL interaction was sizeable for some cultivars, but the wide‐adaptation response exhibited by Flecha suggests that the selection of germplasm adapted to a fairly wide range of drought stress levels can be a feasible target for Mediterranean tall fescue. This finding contrasts with evidence for Mediterranean germplasm of cocksfoot, in which selection for specific adaptation to high or low drought stress is justified by the much wider extent of GL interaction (Pecetti et al. 2009).…”
Section: Discussioncontrasting
confidence: 94%
“…Crossover GL interaction was sizeable for some cultivars, but the wide‐adaptation response exhibited by Flecha suggests that the selection of germplasm adapted to a fairly wide range of drought stress levels can be a feasible target for Mediterranean tall fescue. This finding contrasts with evidence for Mediterranean germplasm of cocksfoot, in which selection for specific adaptation to high or low drought stress is justified by the much wider extent of GL interaction (Pecetti et al. 2009).…”
Section: Discussioncontrasting
confidence: 94%
“…Perennial forages such as tall fescue or cocksfoot can be a valuable alternative to annuals, if they can survive across successive summer droughts. Although most of the temperate origin cultivars available on the market are not drought persistent in Mediterranean areas ), a few cultivars with summer dormancy (Volaire and Norton, 2006) can tolerate severe successive droughts and survive in environments with annual rainfall as low as 300 mm Pecetti et al, 2009Pecetti et al, , 2011. Under chronic water shortages, perennial forage species have a number of advantages in comparison to the predominantly used annual species including (i) fewer inputs with less field preparation and fertilizer requirement, (ii) year-around soil cover reducing the risk of intense soil erosion, (iii) optimal use of water throughout all seasons, thus enhancing forage production in particular in autumn when cereals and annual species are not yet established and (iv) greater flexibility because of the multiple uses of these species (grazing, hay, silage).…”
Section: å Ergon Et Al European Journal Of Agronomy 92 (2018) 97-106mentioning
confidence: 99%
“…Summer dormancy is a trait which has evolved primarily for enhancing plant survival and is expressed by some of the cool-season perennial grasses mainly originating in semi-arid and arid Mediterranean climates where the summer-dry period typically lasts 4 months or more (Cooper 1963). Recent research has demonstrated this trait to be very powerful in improving survival over long and intense dry spells in the field with a suite of papers demonstrating the utility of the trait in cocksfoot and tall fescue in the Mediterranean Basin (Volaire 2002;Volaire et al 2005;Norton et al 2006a;Norton et al 2006b;Shaimi et al 2009;Pecetti et al 2009;Annicchiarico et al 2011), southern USA (Malinowski et al 2005;Malinowski et al 2009) and southeastern Australia (Culvenor and Boschma 2005;Norton et al 2001;Hackney et al 2006;Hayes et al 2010a).…”
Section: Summer Dormancy To Improve Survival Of Extended Extreme Dromentioning
confidence: 99%